Some regularities of memory of visual information - Rimkutė, E.; Lipeikaitė, N. (Psichologija, 1982)
The article deals with the regularities of memory and retention of the visual material. The first experiment is devoted to the immediate recall and recognition of 9 line drawings exposed for 5 seconds at 3x3 matrixes. Thus, it has been established that on the average 3.9 pictures are recalled and 5.8 pictures are recognized from one collection. The recall of the objects depends on their position in the matrix. The majority of the pictures are recalled in the left upper corner. Proceeding from the left to the right and descending from the top to the bottom, the recall becomes lesser. In the second experiment under the same conditions, the complex pictures were exposed and their immediate and 24-hour recalls have been studied. It has turned out that the immediate and the delayed recalls are not essentially different and their average quantities are accordingly 6.3 and 5.9 objects. According to the total results of the group under investigation, it has been determined that the frequency of the recall of objects depends not upon their place in the presented space, but upon the hierarchy of their importance while perceiving the picture. Side by side with the adequate recalls, the most characteristic types of reconstruction are analysed and described. The results of the experiments give evidence as for the role of the schemes which are formed in man's cognition.